2010
DOI: 10.1590/s0102-311x2010000700025
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Brazilian governmental health agencies shows conflicting recommendations concerning oral hygiene practices for children

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0
5

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 9 publications
2
2
0
5
Order By: Relevance
“…At the technical level, we already know that oral health programming adopts an incomplete rationale. An apparently trivial example suffices to back this assertion: a study on programming oral hygiene in children showed that among the 54 public health agencies surveyed (including the Ministry of Health and the Health Departments of Brazil's States and State capitals), the guidelines were inconsistent and conflicting and could be associated with an apparent gap in the scientific evidence 3 . In the 21 st century it is apparently impossible to consistently operationalize oral hygiene practices, much less the more complex interventions at the individual and collective levels.…”
Section: Samuel Jorge Moysés 12mentioning
confidence: 99%
“…At the technical level, we already know that oral health programming adopts an incomplete rationale. An apparently trivial example suffices to back this assertion: a study on programming oral hygiene in children showed that among the 54 public health agencies surveyed (including the Ministry of Health and the Health Departments of Brazil's States and State capitals), the guidelines were inconsistent and conflicting and could be associated with an apparent gap in the scientific evidence 3 . In the 21 st century it is apparently impossible to consistently operationalize oral hygiene practices, much less the more complex interventions at the individual and collective levels.…”
Section: Samuel Jorge Moysés 12mentioning
confidence: 99%
“…A mesmas distorções foram relatadas em relação à freqüência da escovação, variando entre pelo menos 1x/dia até após cada refeição ou consumo de açúcar ou medicamento. (SANTOS et al, 2010).…”
Section: Como As Entidades Ou Comitês Especializados Tem Se Posicionaunclassified
“…Como decorrência natural, vários estudos demonstram o desconhecimento dos pediatras acerca das questões de saúde bucal e a falta de orientação adequada das famílias (FREIRE et al, 2000;MALTZ;LACERDA, 2001;BUZALAF et al, 2006;TEIXEIRA et al, 2010). Para além do âmbito do atendimento pediátrico, um estudo recente mostra que os órgãos governamentais brasileiros fornecem recomendações divergentes e não apoiadas em evidências científicas sobre higiene bucal em crianças (SANTOS et al, 2010).…”
Section: Uma Negligência Histórica E Um Olhar Enviesadounclassified